ISOLATION AND IDENTIFICATION OF FUNGI ASSOCIATED WITH COMPOSTING PROCESS OF MUNICIPAL BIOSOLID WASTE - Thu Hang, Pham Thi; Quynh Tram, Le Thi; Anh, Tran Phuong; Thi Khai Mui, Ho To; Thao Vi, Dang Nguyen; Dang Khoa, Dinh Hoang (Vietnam Journal of Biotechnology, 2018)
Organic waste is gradually degraded during composting process, producing carbon dioxide, water, heat, and humus, the relatively stable end product. The degradation process is carried out by living organisms, of which fungi appear to have the most important role since they break down tough debris (cellulose, lignin, and other resistant materials), enabling other microorganisms to continue the decomposition process. The objective of this study was to isolate and identify the fungi associated with large scale municipal biosolid waste composting process in Vietnam. In this study, we have isolated 10 morphologically different fungal strains from the composting materials, and classified based on morphological characteristics and 18S rDNA sequences. The results showed that these fungal strains belonged to four different genera, including Aspergillus, Penicillium, Monascus, and Trichoderma. The results would be a useful reference for further studies of diversity, and functions of fungi that involved in municipal biosolid waste composting process in Vietnam environmental conditions.